Dynamic-ACTS - A Dynamic Graph Analytics Accelerator For HBM-Enabled FPGAs - Jaiyeoba, Oluwole; Skadron, Kevin (ACM transactions on reconfigurable technology and systems)
Graph processing frameworks suffer performance degradation from under-utilization of available memory bandwidth, because graph traversal often exhibits poor locality. A prior work, ACTS [24], accelerates graph processing with FPGAs and High Bandwidth Memory (HBM). ACTS achieves locality by partitioning vertex-update messages (based on destination vertex IDs) generated online after active edges have been processed. This work introduces Dynamic-ACTS which builds on ideas in ACTS to support dynamic graphs. The key innovation is to use a hash table to find the edges to be updated. Compared to Gunrock, a GPU graph engine, Dynamic-ACTS achieves a geometric mean speedup of 1.5X, with a maximum speedup of 4.6X. Compared to GraphLily, an FPGA-HBM graph engine, Dynamic-ACTS achieves a geometric speedup of 3.6X, with a maximum speedup of 16.5X. Our results also showed a geometric mean power reduction of 50% and a mean reduction of energy-delay product of 88% over Gunrock. Compared to GraSU, an FPGA graph updating engine, Dynamic-ACTS achieves an average speedup of 15X.